Thieno[3,2-b]thiophene and triphenylamine-based hole transport materials for perovskite solar cells - Isci, Recep; Unal, Melis; Yesil, Tamer; Ekici, Alper; Sütay, Berkay; Zafer, Ceylan; Ozturk, Turan (Frontiers in Materials, 2023)
Heterocyclic compounds have played significant roles in achieving high performance as hole transport materials (HTMs) for perovskite solar cell (PSC) applications. Various studies have focused on the development of fused heterocyclic conjugated structures for hole transport materials. In this report, three novel π-extended conjugated materials (M1-M3), based on thieno[3,2-b]thiophene (TT) and 4,4′-dimethoxytriphenylamine [TPA(OMe)2], were designed and successfully synthesized via Palladium (0) catalyzed Suzuki coupling reaction. Their optical, electrochemical, and thermal properties were investigated by UV-Vis, fluorescence, cyclic voltammetry, and thermal analysis. The materials were utilized as hole transport materials in p-i-n architecture perovskite solar cells, which displayed performances of open-circuit voltage (Voc) as high as 1,050 mV, a maximum short-circuit current (Jsc) of 16,9 mA/cm2, a maximum fill factor (FF) of 29.3%, and a power conversion efficiency (PCE) of 5.20%. This work demonstrated that thieno[3,2-b]thiophene and TPA(OMe)2-based structures are promising cores for high-performance hole transport materials in perovskite solar cell architecture.